2015
DOI: 10.1016/j.neuroimage.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk for Alzheimer's disease alters the five-year trajectory of semantic memory activation in cognitively intact elders

Abstract: Healthy aging is associated with cognitive declines typically accompanied by increased task-related brain activity in comparison to younger counterparts. The Scaffolding Theory of Aging and Cognition (STAC) (Park and Reuter-Lorenz, 2009; Reuter-Lorenz and Park, 2014) posits that compensatory brain processes are responsible for maintaining normal cognitive performance in older adults, despite accumulation of aging-related neural damage. Cross-sectional studies indicate that cognitively intact elders at genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 72 publications
(92 reference statements)
5
57
1
Order By: Relevance
“…The higher node degree identified a greater need for compensation, suggesting more severe disease. As the disease progressed, the abilities of the brain to provide effective compensation would eventually diminish, at which time patients show severe cognitive deficits (Rao et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The higher node degree identified a greater need for compensation, suggesting more severe disease. As the disease progressed, the abilities of the brain to provide effective compensation would eventually diminish, at which time patients show severe cognitive deficits (Rao et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies focus on the hippocampus, due to its known relationship with early AD pathogenesis [6]. Some longitudinal studies have demonstrated that cognitively intact elders possessing the ε4 allele experience greater hippocampal atrophy over time compared to non-carriers [79], although these results have not been demonstrated in other studies [1012]. Notably, most of these studies measured the rate of atrophy based on two MRI assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the physically active ε4 carriers had greater semantic memory-related activation compared to the group of physically inactive ε4 carriers (Smith et al, 2011), which we have shown to predict cognitive stability over 18 months (Woodard et al, 2010). This pattern of activation appears to reflect a successful neural compensatory response over 5 years (Rao et al, 2015). In contrast, the combination of being physically inactive and at increased genetic risk for AD, despite being cognitively intact with normal hippocampal volumes at baseline, resulted in greater probability of cognitive decline and hippocampal atrophy over 18-months (Smith et al, 2014; Woodard et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…We recently published a series of papers that have examined the moderating effect of PA on indices of brain structure and brain function based on a cohort of healthy older adults who participated in a 5-year longitudinal observational study (Rao et al, 2015). We previously reported that over an 18-month period, greater levels of PA in APOE-ε4 allele carriers significantly reduced the risk for cognitive decline (Woodard et al, 2012) and preserved hippocampal volume (Smith et al, 2014) compared to physically inactive carriers.…”
Section: Introductionmentioning
confidence: 99%